Management of an urban lagoon. Study case: Ilusiones Lagoon, Tabasco, Mexico - Hernandez-Ramon, Juan Antonio; Priego-Hernandez, Gaston; Plesiński, Karol K.; Rivera-Trejo, José Guadalupe Fabián (Ecosistemas y Recursos Agropecuarios, 2023)
As a delta, Tabasco, located in the Mexican southeast, is susceptible to flooding. The city of Villahermosa, the capital of Tabasco, is not an exception. The most recent event occurred in November 2020, when an excess of rain provoked an urban lagoon to exceed its levels. The lagoon discharges at a river by a diversion channel controlled by a culvert. To analyze it, a hydraulic model -HEC RAS V6.0- was used. Precipitation, flow, and level data recorded during 2020 were used to simulate four scenarios: I) one culvert of 1.5 m x 1.75 m (current situation); II) three culverts of 1.5 m x 1.75 m; III) three culverts of 2 m x 2.5 m; and IV) one culvert of 10 m x 2.5 m. The dimensions of the culverts were subject to the available physical space of the discharge channel. It was found that the best performance was achieved with scenario II. This result is contrasting because this alternative is not the largest as might be expected; it is also encouraging because it improves the performance of this lagoon. With this proposal, we reduce the damage by 75.31%, which means 296 homes are protected. Finally, the proposed methodology can guide designers and decision-makers to evaluate hydraulic works in urban lagoons like those presented in this work.